Intermetallic formation of nickel-palladium kovar lids on ceramic microelectronic packages - Lagar, Jason H.; Mena, Manolo G. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Palladium (Pd) was added in between the nickel (Ni) and gold (Au) flash layer in a Kovar (Fe-Ni-Co alloy) lid of a side-brazed dual in-line ceramic package of a microelectronic product. The addition of Pd and a thinner Au flash layers will bring significant cost savings in the manufacturing of this type of package. lntermetallic formation and material diffusion specifically of the Pd was investigated after subjecting the samples to solder sealing at 330°C, 3X reflow soldering at 260°C and thermal ageing at 200°C and 400°C, each for 168 hours. Through the use of backscattered electron imaging in a Scanning Electron Microscope and Energy Dispersive X-ray analysis, plateshaped and needle-shaped PdSn4 intermetallics were found to form in the bulk Au/Sn solder matrix after reflow soldering and ageing at 200°C. At the Kovar lid/solder interface, a Pd-Au-Sn IMC was formed after solder sealing, reflow soldering and thermal ageing at 200°C. This Pd-Au-Sn IMC was either a binary Pd3Sn2(Au) or binary AuSn(Pd). After thermal ageing at 400°C, Ni3Sn, (Pd,Ni)Snx and (Au,Pd,Ni)Snx were found at the lid/solder interface. At the solder/Co-Ni interface of the ceramic package, a Pd-Au-Sn IMC was also identified together with AuSn but (Au,Pd,Ni)Snx layer was formed after thermal ageing at 400°C. Presence of Kirkendall voids were also found in all conditions. A procedure for determining the mechanical seal strength of the Kovar lids was developed using a customized sample jig and blade holder in a universal tension/compression tester with a digital force gauge. The results showed that ageing at 200°C had the highest force required to break the lid seal while 3X reflow soldering at 260°C had the lowest value. The presence of PdSn4 dispersed in the solder matrix favored the lid seal strength. The presence of isolated area thickening or nodular Pd-Au-Sn lMC on the Ni/solder interface had also provided a better support on the lid seal. The formation of Ni-based IMC after 400°C ageing was more beneficial to the mechanical strength of the interface. Results of hermeticity test involving fine leak and gross leak tests showed that formation of Kirkendall voids had an effect after ageing at 200°C and 400°C. Micro-Computed Tomography (μCT) scan results indicated that voids in the seal were already present after solder sealing. No effect on the voids was noted after the succeeding
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Nickel.#0.; Palladium.#0 -- Iron-nickel-co.; Herme